Thematic Learning Based on Local Wisdom in the New Normal Time in Elementary School - Yesi Murwati; Bambang Sumardjoko; Minsih; Yeny Prastiwi (Jurnal Pendidikan Indonesia, 2022)
Thematic learning based on local wisdom, it is hoped that it can improve knowledge and learning outcomes and provide useful experiences for students. The purpose of this study is to analyses the planning, implementation and constraints of thematic learning based on local wisdom in the new normal period in elementary schools. The subjects of this study were classroom teachers and elementary school students. The method used is a qualitative method of phenomenology. This study uses interview, observation, and documentation guidelines. The data analysis technique used in this study consisted of three stages, namely data reduction, data presentation, and drawing conclusions. The result of study found that, before carrying out thematic learning based on local wisdom, the teacher carries out planning by preparing learning tools. Students learn directly from nature and to increase students' awareness of nature, so that students can maintain and preserve local wisdom and love local wisdom in their area. The obstacle for teachers in the process of implementing local wisdom-based thematic learning in elementary schools is that the time allocation for thematic learning is still lacking and there is no integration between local wisdom learning materials in the curriculum that has been made by the school.